2024
DOI: 10.1093/toxsci/kfae050
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying aryl hydrocarbon receptor-driven divergent macrophage function

Keegan Malany,
Xiaohan Li,
Christoph F A Vogel
et al.

Abstract: Macrophages play an essential role in the innate immune system by differentiating into functionally diverse subsets in order to fight infection, repair damaged tissues, and regulate inappropriate immune responses. This functional diversity stems from their ability to adapt and respond to signals in the environment, which is in part mediated through aryl hydrocarbon receptor (AHR)-signaling. AHR, an environmental sensor, can be activated by various ligands, ranging from environmental contaminants to microbially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…Indole and I3A are endogenous ligands of AHR and we found that decreased circulating abundance of these ligands in offspring of WD-fed dams (and offspring of GF recipients of maternal WD-exposed microbes) was associated with decreased AHR signaling at PND21. AHR has been shown to exert pleiotropic effects in macrophages that are highly dependent on the microenvironment in vivo [83]. In our model, we found that the combination of exposure to maternal and post-weaning WD suppresses AHR signaling and dampens the immune response of BMDMs to LPS.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Indole and I3A are endogenous ligands of AHR and we found that decreased circulating abundance of these ligands in offspring of WD-fed dams (and offspring of GF recipients of maternal WD-exposed microbes) was associated with decreased AHR signaling at PND21. AHR has been shown to exert pleiotropic effects in macrophages that are highly dependent on the microenvironment in vivo [83]. In our model, we found that the combination of exposure to maternal and post-weaning WD suppresses AHR signaling and dampens the immune response of BMDMs to LPS.…”
Section: Discussionmentioning
confidence: 58%
“…AHR is expressed in many cell types, including macrophages, and mediates cellular responses to environmental toxins and dietary metabolites [83]. Acting through STAT3, AHR activation upregulates expression of IL-10 to reduce inflammatory injury [83], suggesting that AHR has immunoregulatory functions that contribute to resolving inflammation and promoting tissue repair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AHR is expressed in many cell types, including macrophages, and mediates cellular responses to environmental toxins and dietary metabolites [ 78 ]. Acting through STAT3, AHR activation upregulates expression of IL-10 to reduce inflammatory injury [ 78 ], suggesting that AHR has immunoregulatory functions that contribute to resolving inflammation and promoting tissue repair.…”
Section: Discussionmentioning
confidence: 99%
“…AHR is expressed in many cell types, including macrophages, and mediates cellular responses to environmental toxins and dietary metabolites [ 78 ]. Acting through STAT3, AHR activation upregulates expression of IL-10 to reduce inflammatory injury [ 78 ], suggesting that AHR has immunoregulatory functions that contribute to resolving inflammation and promoting tissue repair. Indole and I3A are endogenous ligands of AHR, and we found that decreased circulating abundance of these ligands in offspring of WD-fed dams (and offspring of GF recipients of maternal WD-exposed microbes) was associated with decreased AHR signaling at PND21.…”
Section: Discussionmentioning
confidence: 99%